2007
DOI: 10.1037/1064-1297.15.2.187
|View full text |Cite
|
Sign up to set email alerts
|

Moderate drug use and delay discounting: A comparison of heavy, light, and never smokers.

Abstract: Delay discounting was examined in light smokers (10 or fewer cigarettes per day) and compared with previously published delay discounting data for heavy and never smokers. Participants evaluated several hypothetical outcomes: money gains and loses ($10, $100, and $1,000), health gains and losses (durations of improved and impoverished health subjectively equivalent to $1,000), cigarette gains and losses (amounts subjectively equivalent to $1,000), and potentially real rewards ($10 and $100). Light smokers disc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

27
209
7
7

Year Published

2010
2010
2019
2019

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 227 publications
(250 citation statements)
references
References 36 publications
27
209
7
7
Order By: Relevance
“…Richards, Zhang, Mitchell, & de Wit (1999) reduced the number of attempts required to estimate the indifference points from an amount adjustment procedure (i.e., to at least 74 and at most 103), which was reproduced in later studies (Baker et al, 2003;Johnson et al, 2007). Starting with a fixed delayed amount, two upper limits (maximum and minimum) and two lower limits (maximum and minimum) were always established for the changes, which changed according to the previous choices of the subjects.…”
Section: Delay Discounting Tasksmentioning
confidence: 99%
See 1 more Smart Citation
“…Richards, Zhang, Mitchell, & de Wit (1999) reduced the number of attempts required to estimate the indifference points from an amount adjustment procedure (i.e., to at least 74 and at most 103), which was reproduced in later studies (Baker et al, 2003;Johnson et al, 2007). Starting with a fixed delayed amount, two upper limits (maximum and minimum) and two lower limits (maximum and minimum) were always established for the changes, which changed according to the previous choices of the subjects.…”
Section: Delay Discounting Tasksmentioning
confidence: 99%
“…Typical studies offer the choice alternatives in series with determined delays and amounts of money. Such studies usually present five (Patak & Reynolds, 2007), seven (Johnson, Bickel, & Baker, 2007;Myerson et al, 2003), or eight delays (Gonçalves, 2005;Myerson & Green, 1995) that can begin with 6 h (Robles & Vargas, 2008) or 1 day (Johnson et al, 2007) and reach 25 years (Gonçalves, 2005;Johnson et al, 2007;Robles & Vargas, 2008). The amounts can start at $1 (Green et al, 1996) or $10 (Johnson et al, 2007) and end at $100 (Odum & Rainaud, 2003), $1,000 (Robles & Vargas, 2008), or $10,000 (Green et al, 1996), with a total of 25 (Odum & Rainaud, 2003), 27 (Bickel, Odum, & Madden, 1999;Ohmura et al, 2006), or 30 amounts (Gonçalves, 2005), depending on the objectives of the study.…”
Section: Delay Discounting Tasksmentioning
confidence: 99%
“…A second goal was to extend the measure of reliability beyond hypothetical monetary amounts. A number of researchers (e.g., Chapman, 1996;Hardisty & Weber, 2009;Johnson, Bickel, & Baker, 2007) have examined whether individuals display a single, general rate of discounting or whether their rates of discounting differ across commodities. Several investigations have shown that there are absolute differences in the rates of discounting of different commodities, although it is sometimes difficult to determine whether these differences represent differences between commodities themselves or whether the results are confounded by differences in the magnitude of the commodities presented to the participants (see Hardisty & Weber, 2009, for a more detailed discussion).…”
mentioning
confidence: 99%
“…It is therefore possible to quantify the level of impulsivity of human individuals: some are more impatient, which means that people discount the future to a greater or lesser extent [13]. This level of impulsivity is associated with some pathogenic behaviours; the k value of the hyperbolic function describing impulsivity during a monetary choice has been found to be higher in different forms of addiction (smoking [14], alcohol habits [15], addictions to various kinds of drugs [16]), and, recently, in depressive patients [17] and obese women [18].…”
Section: Neuroeconomics and The Force Of Our Desiresmentioning
confidence: 99%